Design and Calibration of a Specialized Polydioptric Camera Rig - Mazhar, Osama; Jamaluddin, Ahmad Zawawi; Jiang, Cansen; Fofi, David; Seulin, Ralph; Morel, Olivier (Frontiers in ICT, 2017)
It has been observed in the nature that all creatures have evolved highly exclusive sensory organs depending on their habitat and the form of resources availability for their survival. In this project, a novel omnidirectional camera rig, inspired from natural vision sensors, is proposed. It is exclusively designed to operate for highly specified tasks in the field of mobile robotics. Navigation problems on uneven terrains and detection of the moving objects while the robot is itself in motion are the core problems that omnidirectional systems tackle. The proposed omnidirectional system is a compact and a rigid vision system with dioptric cameras that provide a 360 degrees field-of-view in horizontal and vertical, with no blind spot in their site combined with a high-resolution stereo camera to monitor anterior field-of-view for a more accurate perception with depth information of the scene. Structure-from-motion algorithm is adapted and implemented to prove the design validity of the proposed camera rig and a toolbox is developed to calibrate similar systems.